Identifying the Factors Affecting the Management of Addiction Treatment Clinics: A Qualitative Study - Iraj Abdi; Ali Komeili; Leila Riahi; Seyed Jamaledin Tabibi (Baqiyatallah University of Medical Sciences, 2020)
Background: Due to the expansion of addiction treatment clinics and the costs that these clinics incur on the government and the families of addicts, monitoring the performance of these clinics and the need to pay attention to the principles of management, efficiency, and effectiveness is essential. Objectives: The present study was conducted to identify the factors affecting the management of addiction treatment clinics. Methods: The present study is a descriptive-applied and cross-sectional study conducted in 2019. Experts and academic experts have been considered as the research community, and 18 people were selected as the research sample by the purposeful snowball method. Data collection tools were the review of relevant national and international documents as well as semi-structured exploratory interviews. Finally, after collecting information from the interview sections and reviewing the sources, the data foundation and coding methods (open, axial, and selective) were used to classify the data.Results: The findings of the study showed that the effective factors in the management of addiction treatment clinics are dimensions such as organization, planning, control, guidance as well as leadership and treatment management. Conclusion: According to the findings of this study, it can be concluded that the effective factors in the management of addiction treatment clinics can be a good basis to evaluate managers so that the policies and programs of the organization can be upgraded, modified, and reviewed.